The Effects of Experience, Instruction and Personality Factors on Complex Problem Representation and Performance in Auditing: An Experimental Investigation - Lehmann, Constance M (ProQuest Dissertations & Theses, 2001)
The purpose of this study was to investigate complex problem representation and judgment accuracy by several groups of accounting students and auditing professionals. In addition, the relationships of personality factors, experience and ability were examined. A total of 169 subjects participated, ranging from students just starting a five-year professional accounting program to partners/shareholders in public accounting firms. The subjects completed a hypothetical case where they assessed the financial condition of the company and judged its ability to continue as a going concern for the next 12 months and the type of report they would issue. They were also asked to list the additional information they would request and testing they would do to confirm their judgment. The results suggested that, similar to the findings in the medical expertise development research, the number of concepts, causation links, and summaries included in the subjects' problem representations of the case company's financial condition were negatively related to the number of months of subjects' professional auditing experience. The number of additional information items requested and the number of additional tests requested by the subjects to confirm their decision about the case company's financial condition was also negatively related to months of experience. Interestingly, the measures of judgment accuracy (the likelihood percentage of company survival for the next 12 months and the type of report that the subject would issue) were not associated with months of experience, although there were significant differences between the subjects that had taken only one auditing class and the subjects that had taken more than one auditing class. The measures of general problem-solving ability and personality factors were not related to any of the dependent variables measured in this study. Alternative measures of expertise, such as number of exposures to similar cases did not add explanatory power to a model using just months of experience to predict the problem representation variables. A variable for the number of auditing classes taken and individual goal orientation scores did add incremental explanatory power to the model of expertise.